Biochemical analysis of the TPS-a subfamily in Medicago truncatula - Hendrickson, Hannah; Islam, Monirul; Wabo, Ghislain Fotso; Mafu, Sibongile (Frontiers in Plant Science, 2024)
Terpenes are important mediators of plant chemical response to environmental cues. Here, we describe the genome-wide identification and biochemical characterization of TPS-a members in Medicago truncatula, a model legume crop. Genome mining identified thirty-nine full-length terpene synthases with a significant number predicted to produce monoterpenes and sesquiterpenes. Biochemical characterization of the TPS-a subfamily associated with sesquiterpene biosynthesis revealed such compounds, that exhibit substantial biological activity in other plants. Gene expression analysis using qPCR and the Medicago gene atlas illustrated distinct tissue and time-based variation in expression in leaves and roots. Together our work establishes the gene-to-metabolite relationships for sesquiterpene synthases in M. truncatula. Understanding the biosynthetic capacity is a foundational step to defining the ecological roles of this important family of compounds.